Antimicrobial Peptides in Human Sepsis - Martin, Lukas; van Meegern, Anne; Doemming, Sabine; Schuerholz, Tobias (Frontiers in Immunology, 2015)
Nearly 100 years ago, antimicrobial peptides (AMPs) were identified as an important part of innate immunity. They exist in species from bacteria to mammals and can be isolated in body fluids and on surfaces constitutively or induced by inflammation. Defensins have anti-bacterial effects against Gram-positive and Gram-negative bacteria as well as anti-viral and anti-yeast effects. Human neutrophil peptides (HNP) 1-3 and human beta-defensins (HBDs) 1-3 are some of the most important defensins in humans. Recent studies have demonstrated higher levels of HNP -1-3 and HBD-2 in sepsis. The bactericidal/permeability increasing protein (BPI) attenuates local inflammatory response and decreases systemic toxicity of endotoxins. Moreover, BPI might reflect the severity of organ dysfunction in sepsis. Elevated plasma lactoferrin is detected in patients with organ failure. HNP-1-3, lactoferrin, BPI and heparin-binding protein (HBP) are increased in sepsis. Human lactoferrin peptide 1-11 (hLF 1-11) possesses antimicrobial activity and modulates inflammation. The recombinant form of lactoferrin (talactoferrin alpha, TLF) has been shown to decrease mortality in critically ill patients. A phase II/III study with TLF in sepsis did not confirm this result. The growing number of multiresistant bacteria is an ongoing problem in sepsis therapy. Furthermore, antibiotics are known to promote the liberation of pro-inflammatory cell components and thus augment the severity of sepsis. Compared to antibiotics, AMPs kill bacteria but also neutralize pathogenic factors such as lipopolysaccharide (LPS). The obstacle to applying naturally occurring AMPs is their high nephro- and neurotoxicity. Therefore, the challenge is to develop peptides to treat septic patients effectively without causing harm. This overview focuses on natural and synthetic AMPs in human and experimental sepsis and their potential to provide significant improvements in the treatment of critically ill with severe infections.